2006
DOI: 10.1097/01.pcc.0000227108.38119.2e
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency oscillatory ventilation in pediatric patients with acute respiratory failure

Abstract: In pediatric patients with acute respiratory failure, failing conventional ventilation, HFOV improves gas exchange in a rapid and sustained fashion. However, randomized controlled trials are needed to identify its benefits over conventional modes of mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 34 publications
7
26
1
5
Order By: Relevance
“…As regards oxygenation improvement, we found that HFO significantly improved oxygenation after 24 hours of enrollment, a finding that is comparable with results in several pediatric studies 35,[45][46][47] and adult studies 34,36 . Also survivors among HFO group showed significant higher OI decrease percent, PaO 2 /FiO 2 after 24 hours and higher PaO 2 /FiO 2 increase percent.…”
Section: Volume 59 • Number 2 Hfo Versus CMV In Pediatric Ardssupporting
confidence: 77%
“…As regards oxygenation improvement, we found that HFO significantly improved oxygenation after 24 hours of enrollment, a finding that is comparable with results in several pediatric studies 35,[45][46][47] and adult studies 34,36 . Also survivors among HFO group showed significant higher OI decrease percent, PaO 2 /FiO 2 after 24 hours and higher PaO 2 /FiO 2 increase percent.…”
Section: Volume 59 • Number 2 Hfo Versus CMV In Pediatric Ardssupporting
confidence: 77%
“…To be effective, these modes can require a mean airway pressure 5 cmH 2 O higher than that used with conventional ventilation. This can reduce venous return leading to greater need for fluid resuscitation and vasopressor requirements [612][613][614][615][616].…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…Animal studies have suggested that early institution of HFOV could limit ventilator-induced lung injury. Nonetheless, it appears that HFOV has largely become a rescue therapy when conventional management fails (38,39). A decade ago, a report of 10 pediatric ICUs showed patients were started on HFOV after a mean of 3.3 days of ventilation at a mean OI of 30 (40).…”
Section: Hfovmentioning
confidence: 99%